Emergence of begomoviruses and DNA satellites associated with weeds and intercrops: a potential threat to sustainable production of cassava in Côte d’Ivoire - Aya Ange Naté Yoboué; Aya Ange Naté Yoboué; Bekanvié S. M. Kouakou; Bekanvié S. M. Kouakou; Justin S. Pita; Justin S. Pita; Boni N’Zué; William J.-L. Amoakon; William J.-L. Amoakon; Kan Modeste Kouassi; Kan Modeste Kouassi; Linda Patricia L. Vanié-Léabo; et al. (Frontiers in Plant Science)
Cassava (Manihot esculenta Crantz) plays a significant role in the livelihoods of people in Africa, particularly in Côte d’Ivoire. However, its production is threatened by begomoviruses which cause huge yield losses. Some weeds and food crops intercropped with cassava act as reservoirs, thereby facilitating the sustenance and propagation of Cassava mosaic begomoviruses (CMBs), along with other begomoviruses. To effectively manage these diseases, it is imperative to enhance our understanding of the various hosts of cassava viruses in Côte d’Ivoire. Thus, a comprehensive nationwide survey was conducted in 2017 in cassava fields across Côte d’Ivoire, and molecular analyses were performed on the samples collected. The results obtained from this survey indicated that 65 plant species belonging to 31 families were potential alternative hosts for CMBs in Côte d’Ivoire. The molecular analyses revealed that four species, Capsicum annuum, Solanum melongena, Centrosema pubescens, and Asystasia gangetica exhibited differential affinities for both African cassava mosaic virus and East African cassava mosaic Cameroon virus. Additionally, other begomoviruses and new alphasatellites were identified. Soybean chlorotic blotch virus was isolated from C. pubescens while West African Asystasia virus 1, West African Asystasia virus 2, and a new Asystasia yellow mosaic alphasatellite were isolated from A. gangetica which appears to be a plant species that could favor the emergence of new viral species harmful to cassava cultivation. This study offers insights that will inform the development of more effective control methods for sustainable cassava production in Côte d’Ivoire.